Data justice made tangible, spatial, and actionable : An exploration of everyday data fairness through game making - Tedeschi, Miriam; Gkouskos, Dimitrios; Resmini, Andrea (Sage, 2026)
Data justice is negotiated and performed in everyday micro-actions and spatial settings. Yet it is hard to visualise, unpack and,thus, act upon, as its spatial and actionable characteristics remain hidden: everyday actions tend to be carried out automat-ically, and their data dimension remains, in most cases, not tangible and seemingly not operable. This article explores howdata (in)justice can be made tangible, spatial, actionable and safely experimented with through tabletop game making and pro-totyping. The data was collected in a class setting within the Design Games Framework (DGF), a structure where researchparticipants, ﬁrst, write daily diaries describing their everyday socio-spatial contexts and, second, prototype a tabletop gamereworking existing board games through the relevant topics emerging from the diaries. Results show how the process ofdesigning games to explore data justice discourses and ethical dilemmas, such as fairness and transparency on the use ofdata, or data privacy, enhances actionability over data by making it tangible and spatial.